Quantum Learning Model Influence using Series of Drawings Towards The Fifth Grade Students’ Narrative Writing Skill (Journal of Primary Education, 2018)
This study aims to determine the effect of quantum learning model with the series of drawings media on the learning achievement to write narrative of the fifth grade students of elementary school in The district of Kudus. The type of this research is quasi-experimental with non equivalent controlled group design. The sampling technique used was Cluster Random Sampling followed by purposive sampling technique. The result of n-gain analysis shows that the quantum learning with the drawing media in the control class gets 0.29 with low criteria while the experimental class gets 0.33 with moderate criteria. The ttest results show that tvalue is 5.911 while ttable is 2.006 or tvalue > ttable and the significance of it is 0.000 so H0 is rejected. The linear regression test of the quantum learning model by using series of drawing media towards the learning result of writing essay ability is 97.0%. Based on the data analysis it can be concluded that there is a significant influence on the use of quantum learning models by using a series of drawings as media on the results of students' ability in learning to write narrative essays.